The factors affecting the hydrogen adsorption on Pt/SO4(2-)-ZrO2 catalyst - Triwahyono, Sugeng; Sarmidi, Mohamad Roji; Abdul Aziz, Ramlan; Yamada, T.; Hattori, H. (Kolej Universiti Sains dan Teknologi Malaysia (KUSTEM), 2004)
Hydrogen adsorption was studied for Pt/SO4(2-)-ZrO2 (PSZ) samples modified with Na addition, pyridine preadsorption, and water preadsorption to elucidate the relation between the rate and capacity of hydrogen adsorption and the surface state. The surface states were monitored by XRD, IR, ammonia TPD, and measurement of catalytic activity for cyclohexane isomerization. All the modifications suppressed the hydrogen uptake. It was suggested that Lewis acid sites promote the hydogen uptake by stabilizing spiltover hydrogen atoms.